2016
DOI: 10.2147/tcrm.s123172
|View full text |Cite
|
Sign up to set email alerts
|

High bone turnover elevates the risk of denosumab-induced hypocalcemia in women with postmenopausal osteoporosis

Abstract: Hypocalcemia is the most common major adverse event in patients with osteoporosis receiving the bone resorption inhibitor denosumab; however, limited information is available regarding risk factors of hypocalcemia. Therefore, this study aimed to identify the risk factors of hypocalcemia induced by denosumab treatment for osteoporosis. We retrospectively reviewed the records of patients who had received initial denosumab supplemented with activated vitamin D for osteoporosis. Serum levels of the following bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 33 publications
1
42
0
1
Order By: Relevance
“… 12 , 15 However, increasing attention has been paid to high bone turnover as a risk factor for denosumab-induced hypocalcemia. 11 , 16 , 19 Among these risk factors, our patient had high bone turnover and vitamin D deficiency in the present case. Symptomatic hypocalcemia occurred only once, at 2 weeks following the initial administration, throughout the three courses of denosumab.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“… 12 , 15 However, increasing attention has been paid to high bone turnover as a risk factor for denosumab-induced hypocalcemia. 11 , 16 , 19 Among these risk factors, our patient had high bone turnover and vitamin D deficiency in the present case. Symptomatic hypocalcemia occurred only once, at 2 weeks following the initial administration, throughout the three courses of denosumab.…”
Section: Discussionmentioning
confidence: 52%
“… 17 The generally recognized risk factors for hypocalcemia are renal impairment and lack of prophylactic administration of calcium and activated vitamin D. We recently reported that high bone turnover was also associated with a higher risk of denosumab-induced hypocalcemia in patients with postmenopausal osteoporosis. 16 However, all cases of hypocalcemia in that series were asymptomatic. Here, we present the case of a male patient with symptomatic hypocalcemia and high bone turnover status induced by a single, 60 mg dose of denosumab, even though he was receiving prophylactic vitamin D and had normal renal function.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Phase 3 trials of denosumab in patients with cancer and metastatic bone lesions showed a 5.2% incidence of hypocalcemia, most of which was mild and asymptomatic, but 2% of cases were high-grade (19). Hypocalcemia was also seen in patients receiving denosumab for low bone density if they had concomitant vitamin D deficiency and higher baseline bone turnover rates (20). Small trials in patients with severely reduced renal function have documented a potentially higher incidence of hypocalcemia after treatment with denosumab in this group (21).…”
Section: Discussion Of Questionmentioning
confidence: 99%